Math connects : Grade K - Mary Behr Altieri; Macmillan/McGraw-Hill School Publishing Company (Columbus, OH Macmillan/McGraw-Hill, 2009)
Includes 10 units per grade level where students investigate, apply, and reflect within a real-world context. This title contains blackline masters of the student workbook that are followed by field-tested performance-based assessments developed by MARS (Mathematics Assessment Resource Service) under an NSF grant.
Keywords: Mathematics -- Study and teaching (Primary) Mathematics -- Study and teaching (Elementary)